The Salience of Gender: Female Islamic Authority in Aceh, Indonesia. Issue 4 (1st October 2016) - Kloos, David
Abstract: This article analyses the relationship between gender and religious authority in contemporary Aceh, Indonesia. It focuses on the lives and careers of two female Islamic teachers in different parts of the province. Their authority, it is argued, derives from expertise acquired from prestigious centres of religious learning, careful (if not always successful) negotiation of formal institutions – including the state – and their status as local community leaders. Their views and experiences raise urgent questions about the position of women in Acehnese society and the influence of (the rise of) normative Islam and the state. By asking what, exactly, is "female" about female Islamic authority, and what is not, this article addresses a persistent dichotomy in the literature on Southeast Asia between formal (state and religious) discourses and institutions as a source of male authority and more informal, localised practices and social relations as a domain of female authority.